Inclusive education: pedagogical approach to online versus face-to-face teaching - Baysan, Aylin; Naeem, Usman (Frontiers in Education, 2023)
In today’s educational landscape, active learning is often overlooked during lectures, seminars, and tutorials. The aim of this study was to investigate perceptions of online and face-to-face lecture formats and their impact on the learning experiences of undergraduate dental students in Years 3–5. This qualitative study was conducted to investigate the effectiveness of different lecture formats at the Institute of Dentistry for undergraduate dental students in Years 3–5. There were two specific questions asked to dental undergraduate students with additional free-text questions. In total, 120 of 221 undergraduate students participated in this study between October 2019 and February 2020, and only 42 participants included the free-text comments. Three core themes related to the blended learning approach were identified: (1) scheduled versus recorded lectures, (2) duration of academic lectures, and (3) neurodiversity and learning experiences. The results showed that the learners perceived the traditional didactic lectures as the least effective format. There is not a “one fits all” lecture format that would accommodate a neurodiversity-based approach that focuses on the strengths, abilities, and interests of students. Hybrid lecture formats in combination with online teaching coupled with small group tutorials could be suggested. There is a unique challenge in the post-COVID-19 era for both educators and learners due to the lack of clinical practice and heavy reliance on online methods of teaching in Dentistry. Therefore, the implication of these results on the planning and financing of programmes could be discussed in Higher Education.